Topological Darkness in Self‐Assembled Plasmonic Metamaterials. (18th October 2013) - Malassis, Ludivine; Massé, Pascal; Tréguer‐Delapierre, Mona; Mornet, Stephane; Weisbecker, Patrick; Barois, Philippe; Simovski, Constantin R.; Kravets, Vasyl G.; Grigorenko, Alexander N.
<x xml:space="preserve">Abstract</x> Self‐assembled plasmonic metamaterials are fabricated from silver nanoparticles covered with a silica shell. These metamaterials demonstrate topological darkness or selective suppression of reflection connected to global properties of the Fresnel coefficients. The optical properties of the studied structures are in good agreement with effective medium theory. The results suggest a practical way of achieving high phase sensitivity in plasmonic metamaterials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>